Writing in the discipline - Dapito, Cheniza P.; Salvosa, Auxilie Aurora S.;Tiburcio, Paciencia Q.;Pagay, Jenalyn S.;Tagasa, Gina C. (Makati City, Philippines : Grandwater Publication and Research Corporation, 2004)
This book is written in response to the critical thinking and writing skills needed to communicate in classes and in the workplace.
Preface -- Part 1. Paragraph writing -- Part 2. The Business correspondence -- Part 3. The Research paper -- Part 4. Technical report writing.
Keywords: REPORT WRITING -- RHETORIC -- ENGLISH LANGUAGE